PEMBIAYAAN KESEHATAN DAN PERAN PEMERINTAH DALAM PELAYANAN KESEHATAN - Lia Sopiani; Maria Ulfa; Zaini; Yuni Andriana; Ifayatul Ahyani; Nila Agustin; Yulia Rohmiati Hamri; Lale Ajeng Khalifatun Wardani (Nusadaya Journal of Multidiciplinary Studies, 2022)
Health financing is one of the fields of science in health economics. What is meant by health costs is the amount of funds that must be provided by individuals, families, community groups. Sources of health costs can come from the government budget, community budgets, domestic and foreign assistance, as well as a combination of government and community budgets. In general, health costs can be divided into two, namely the cost of medical services and the cost of public health services. The main requirements for health financing are the amount, distribution and utilization. While the function of financing is to extract funds, multiply funds. The main problems in health financing include the lack of available funds, inappropriate distribution of funds, inappropriate use of funds, imperfect management of funds and increasing health costs. While the settlement efforts taken include increasing the amount of funds, improving the distribution, utilization and management of funds, as well as controlling health costs.